2021
DOI: 10.1136/bmjgast-2021-000641
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of covered stents for transjugular intrahepatic portosystemic stent shunt in patients with variceal bleeding and refractory ascites secondary to cirrhosis

Abstract: ObjectivesTransjugular intrahepatic portosystemic stent shunt (TIPSS) is clinically effective in variceal bleeding and refractory ascites; however, the cost-effectiveness of TIPSS has yet to be evaluated in the UK. This study aimed to establish the cost-effectiveness of (i) pre-emptive TIPSS versus endoscopic band ligation (EBL) in populations with variceal bleeding and (ii) TIPSS versus large volume paracentesis (LVP) in refractory ascites.MethodsA cost-utility analysis was conducted with the perspective incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…United Network for Organ Sharing data from 2002 to 13 indicated that patients with TIPSS had increased chances of surviving to receive liver transplant, reinforcing its role as a bridge in this setting 13. In addition, TIPSS has shown to be cost-effective in comparison to LVP, with an increase in 0.526 QALY and a saving of £17 983 per patient 14. Poor synthetic function (bilirubin >50 mmol/L and/or platelets <75×10 9 /L) is associated with poor outcomes and are relative contraindications 15…”
Section: Tipss For Refractory Ascitesmentioning
confidence: 99%
“…United Network for Organ Sharing data from 2002 to 13 indicated that patients with TIPSS had increased chances of surviving to receive liver transplant, reinforcing its role as a bridge in this setting 13. In addition, TIPSS has shown to be cost-effective in comparison to LVP, with an increase in 0.526 QALY and a saving of £17 983 per patient 14. Poor synthetic function (bilirubin >50 mmol/L and/or platelets <75×10 9 /L) is associated with poor outcomes and are relative contraindications 15…”
Section: Tipss For Refractory Ascitesmentioning
confidence: 99%
“…For the consideration of a possible introduction of the TIPS procedure in endemic regions, cost efficiency is one of the decisive criteria. Recent studies from Europe or North America have assessed the cost of TIPS procedure in patients with liver cirrhosis, which ranged from £4,646 (currently €5,509) [37] to $50,865.94 (currently €43,692) [38]. Since these calculations do not itemize personnel costs, consumables, profit margins, or basic technical equipment, a transfer to the economic situation in endemic regions is hardly possible.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mattock et al, TIPS resulted in 0.526 additional QALYs, saving £17,983 per patient and had a 100% probability of being cost-effective and cost-saving when compared with LVP. 67 The major savings were from avoided LVP sessions, fewer variceal bleeds, reduced SBP, fewer catheter failures, and fewer hospital bed days. With TIPS there is more cost incurred with mild HE, but a 100% probability of being cost-effective and cost saving when compared with LVP.…”
Section: Tips Vs Lvp Updatementioning
confidence: 99%